Translanguaging as a Cultural Practice: A Critical Discourse Analysis of Indonesian Pop Culture for Reframing Bilingual Education in a Multicultural Society - Haikal Romadhan Al Yusad; Diaarkan Ombakkita (Tunjuk Ajar: Journal of Education and Culture, 2026)
This study examines how translanguaging works as a cultural practice in Indonesian popular culture and what this implies for bilingual education. The corpus comprises 40 multimodal texts: 10 popular song lyrics from YouTube (2020–2025), 10 Instagram and TikTok excerpts, and 20 scene transcripts from Indonesian films and television series. Data were analysed using Norman Fairclough’s three-dimensional model of Critical Discourse Analysis, covering textual, discursive practice, and socio-cultural practice dimensions, to identify translanguaging patterns together with their ideological functions. The analysis shows that translanguaging here is a deliberate and creative communicative strategy that widens audience reach, shapes hybrid identities, and negotiates socio-cultural meanings, rather than a stylistic accident. The practice quietly unsettles monolingual ideologies of the national language by normalising linguistic diversity and projecting a more inclusive, plural national identity. At the same time, the data reveal an internal tension: English tends to accrue prestige and can reproduce new hierarchies among languages. The gap between everyday multilingual practice and the rigid separation models still common in bilingual education motivates a pedagogical reorientation. The article proposes translanguaging pedagogy that treats learners’ full linguistic repertoires as educational capital, supported by curriculum integration of relevant pop culture texts, assessment reform, and teacher professional development so that Indonesian bilingual education can become more responsive, inclusive, and linguistically just.